Theoretical Predictions, Experimental Modulation Strategies, and Applications of MXene‐Supported Atomically Dispersed Metal Sites. Issue 13 (16th December 2021) - Gu, Hongfei; Li, Xinyuan; Zhang, Jiatao; Chen, Wenxing
Abstract: Atomically dispersed metal sites (ADMSs) attract immense attention because they can be used in the fields of energy and environmental protection as they are characterized by high atomic utilization efficiency and exhibit high activity. Various supports for anchoring isolated metal atoms are developed to construct ADMSs characterized by highly stable and well‐defined structures. This can be achieved by increasing the number of anchoring sites and reinforcing metal–support interactions. MXenes, a new series of 2D nanomaterials, exhibit promising potential in stabilizing isolated metal atoms because of their large specific surface areas and unique surface properties. The high conductivity and hydrophilicity of MXenes can be attributed to the nature of surface functionalization and the properties of tunable structures of the materials. Benefiting from these excellent properties, MXenes can find their applications in various fields. Herein, the precise characterization methods that can be followed to study ADMSs, the construction of MXene‐supported ADMSs using theoretical predictions, and experimental modulation strategies are summarized, and their corresponding applications in electrocatalysis, organocatalysis, and advanced battery systems are systematically illustrated. It is hoped that this review will provide insights that can be used for the further development of MXene‐supported ADMSs. Abstract : Focusing on the rapid development of MXene‐supported atomically dispersed metal sites (ADMSs), excellent characterization methods of ADMSs, recent progress of MXene‐supported ADMSs from the aspects of theoretical predictions, experimental modulation strategies and their corresponding applications in electrocatalysis, organocatalysis and advanced battery systems, are summarized. It is hoped that this review can provide more insights for researchers working on MXene‐supported ADMSs.